Spectral library of European pegmatites, pegmatite minerals and pegmatite host-rocks – the GREENPEG project database - Cardoso-Fernandes, Joana (2023)
The New Exploration Tools for European Pegmatite Green-Tech Resources (GREENPEG) spectral database contains the spectral signature, obtained through reflectance spectroscopy studies, of European pegmatites and minerals as well as their host rocks. Samples include pegmatites of the Nb–Y–F (NYF) and Li–Cs–Ta (LCT) chemical types and host rocks from pegmatite locations in Austria, Ireland, Norway, Portugal, and Spain. The database contains the reflectance spectra (raw and continuum-removed spectra), sample photographs, and main absorption features automatically extracted by a self-proposed Python routine. Whenever possible, spectral mineralogy was interpreted based on the continuum-removed spectra. A detailed description of the database, its content and structure, the measuring instrument, and interoperability with geographic information system (GIS) tools is available in this database report. Moreover, examples of how the data can be used and interpreted are also provided. The advantages and added value of the presented dataset reside in its European scale, with representative samples from pegmatites with distinct genesis, mineralogy, structure, and host rocks that can be used as a reference for pegmatite exploration at a global scale via, for example, satellite image processing. The reported spectral mineral assemblages can also be of interest when considering resource estimation or ore processing. Thus, it is expected that this open dataset, available on the Zenodo platform https://doi.org/10.5281/zenodo.6518318 (Cardoso-Fernandes et al., 2022b), will be a reference for distinct types of users, ranging from academia to industry.